2012
DOI: 10.5539/jps.v1n1p14
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus ostreatus and Ruscus aculeatus Extracts Cause Non-Apoptotic Jurkat Cell Death

Abstract: We tested the effect of ethanol extracts from Ruscus aculeatus (Asparagaceae) and Pleurotus ostreatus (Agaricales) on the survival and proliferation of the Jurkat cell line, a model of human acute T-cell lymphocytic leukemia. R. aculeatus extracts were toxic to both Jurkat cells and human primary lymphocytes. P. ostreatus extracts were significantly more toxic to Jurkat cells than primary lymphocytes, as seen by LDH release and MTT assays. Annexin-V detection as well as Bax, Bcl-2, Smac/Diablo, and Caspase-8 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…In turn, the hydroethanolic extracts of the aerial part and roots and rhizomes, as well as the decoction of roots and rhizomes, presented toxicity towards the liver primary cell culture (PLP2). These results are in agreement with those described by Bassil et al [ 23 ], in which they explored the effect of ethanolic extract on leukemia acute lymphocyte cancer proliferation, and concluded that the R. aculeatus extract is not a good candidate for the development of anti-tumor drugs, as it demonstrated a cytotoxic effect, although further studies are needed to confirm this statement.…”
Section: Resultssupporting
confidence: 92%
“…In turn, the hydroethanolic extracts of the aerial part and roots and rhizomes, as well as the decoction of roots and rhizomes, presented toxicity towards the liver primary cell culture (PLP2). These results are in agreement with those described by Bassil et al [ 23 ], in which they explored the effect of ethanolic extract on leukemia acute lymphocyte cancer proliferation, and concluded that the R. aculeatus extract is not a good candidate for the development of anti-tumor drugs, as it demonstrated a cytotoxic effect, although further studies are needed to confirm this statement.…”
Section: Resultssupporting
confidence: 92%
“…The pro‐apoptotic effect of R. aculeatus L. aqueous extract at the concentration of 2 mg/ml in our study was better to A549 cells than T24 (8.14 ± 0.41and 1.72 ± 0.07‐fold higher percentage of early apoptotic‐treated cells comparing to the control cells of the A549 cell line and T24 cell line, respectively). This is higher than that shown by Bassil et al () on Jurkat cell line, despite higher concentration used in their study (8 and 10 mg/ml) and the use of ethanolic instead of aqueous extract of this species. Late apoptosis was significantly more induced by T. communis 1 and 2 mg/ml extract, compared to A. acutifolius and R. aculeatus extracts.…”
Section: Resultscontrasting
confidence: 60%
“…Mushroom natural products and compound has been reported for their pharmacological efficacy against various types of disorders includes cancer (Dias et al, 2012;Harvey, 2008). Medicinal and edible mushroom has been reported to have various potentials i.e., cytotoxic, antiproliferative, and antioxidant (Bassil et al, 2012;Dong et al, 2007;Jiang and Sliva, 2010;Kim et al, 2004;Liu et al, 2009;Thohinung et al, 2010). The mushrooms extracts consist of polysaccharides, proteins,…”
Section: Introductionmentioning
confidence: 99%